If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(-2x + 3) = 32 Reorder the terms: 8(3 + -2x) = 32 (3 * 8 + -2x * 8) = 32 (24 + -16x) = 32 Solving 24 + -16x = 32 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + -16x = 32 + -24 Combine like terms: 24 + -24 = 0 0 + -16x = 32 + -24 -16x = 32 + -24 Combine like terms: 32 + -24 = 8 -16x = 8 Divide each side by '-16'. x = -0.5 Simplifying x = -0.5
| 80-2x=50 | | x-.3x=38000 | | -15x-125=-9x-83 | | -3k^2=-75 | | 6a^2-8ab=0 | | -4x+14y=2 | | -6x+25=-3x+13 | | 3p-14=p | | 18=2t+8 | | -3x-3=-2x-2 | | x^2-88=-7 | | 0.09xX=123.42 | | 11x+21=6x+11 | | p/7=28 | | 15x+50=9x+32 | | 2(3x-4)=7(2x+5) | | 3-(x+2)=1 | | -r/3≤6 | | 28=p/7 | | -20x+24=-12x+16 | | -12x+63=-8x+39 | | -9x+69=-6x+45 | | t-22.4=34.8 | | -77=-9a-5 | | 11x-32=7x-20 | | X-4-5=0 | | -21x-125=-14x-69 | | X+5x=21+15+3x | | 3x=5x+3+10 | | -4x+6=-2x+4 | | (3/8)-(2/10) | | (X-a)/(x-b) |